Traffic Management Of Air Transportation On Noise Control In The Area Around Juanda Airport - Pamungkas, Tri Cahyo Adi; Mudjanarko, Sri Wiwoho (LPPM of NAROTAMA UNIVERSITY, 2021)
This study aims to determine (1) the level of noise in the area around Juanda Airport, (2) the perception of the community in the area around Juanda Airport about the comfort of life with noise, and (3) public perception of the discourse on implementing environmental management in the area around Juanda airport. The locations in this study are on Jalan Raya Sedati Gede (A1) and Jalan H. Abdul Rahman Sedati Gede (A2). The data collection technique used is the measurement technique with the help of a sound level meter for noise data collection, while the public perception data collection uses a questionnaire technique. The analysis technique used for public perception data is to use descriptive statistical tests. The results showed that (1) the measurement results in residential areas were in accordance with the Noise Level Quality Standard Decree of the Minister of Environment, Kep 48 / MENLH / 11/1996. November 25, 1996, for the locations of Jalan Raya Sedati Gede (A1) 77.48 dBA, and Jalan H. Abdul Rahman Sedati Gede (A2) 67.43 Dba above the noise quality standard threshold for settlements of 55 dBA. (2) The majority of the people around Juanda Airport agree that flight activities at Juanda airport cause noise that cause discomfort, rest, and cause stress. (3) The community in the area around Juanda Airport agreed to the need for environmental management as an effort to control noise.